Obesity, but not hypohydration, mediates changes in mental task load during passive heating in females - Caldwell, Aaron R. (PeerJ, 2018)
BACKGROUND: The independent effects of hypohydration and hyperthermia on cognition and mood is unclear since the two stresses often confound each other. Further, it is unknown if obese individuals have the same impairments during hyperthermia and hypohydration that is often observed in non-obese individuals. METHODS: The current study was designed to assess the independent and combined effects of mild hypohydration and hyperthermia on cognition, mood, and mental task load in obese and non-obese females. Twenty-one healthy females participated in two passive heating trials, wherein they were either euhydrated or hypohydrated prior to and throughout passive heating. Cognition (ImPACT), mental task load (NASA-TLX), and mood (Brunel Mood Scale; BRUMS) were measured before and after a 1.0 °C increase in core temperature (T(C)). RESULTS: After a 1.0 °C T(C) elevation, hypohydration resulted in greater (p < 0.05) body mass loss (−1.14 ± 0.48 vs −0.58 ± 0.48 kg; hypohydrated and euhydrated, respectively) and elevation in serum osmolality (292 ± 4 vs 282 ± 3 mOsm; p < 0.05) versus euhydration. Hypohydration, independent of hyperthermia, did not affect mental task load or mood (p > 0.05). Hyperthermia, regardless of hydration status, impaired (∼5 A.U) measures of memory-based cognition (verbal and visual memory), and increased mental task load, while worsening mood (p < 0.05). Interestingly, obese individuals had increased mental task load while hyperthermic compared to the non-obese individuals (p < 0.05) even while euhydrated. Hypohydration did not exacerbate any heat-related effects on cognition between obese and non-obese females (p > 0.05). CONCLUSION: These data indicate that hyperthermia independently impairs memory-based aspects of cognitive performance, mental task load, and leads to a negative mood state. Mild hypohydration did not exacerbate the effects of hyperthermia. However, obese individuals had increased mental task load during hyperthermia.